2018
DOI: 10.1039/c8ob01454j
|View full text |Cite
|
Sign up to set email alerts
|

d-/l-Isothymidine incorporation in the core sequence of aptamer BC15 enhanced its binding affinity to the hnRNP A1 protein

Abstract: Truncation of BC15 and d-/l-isothymidine modification of its core sequence greatly enhanced the binding affinity and selectivity to the hnRNP A1 protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Modifications of the sugar ring can improve nuclease stability and prolong serum half-life. Similarly, the 2'-OH positions of RNA aptamers can be substituted with 2'-F 82 , 83 , 84 , 2'-OMe 85 , 2'-NH 2 , 2'-LNA 86 , 87 , and 2'-d-/l-isonucleoside 88 , 89 . Substitution of non-natural nucleotides into oligonucleotides is achieved by mutating T7 RNA polymerase.…”
Section: Rna Modificationmentioning
confidence: 99%
“…Modifications of the sugar ring can improve nuclease stability and prolong serum half-life. Similarly, the 2'-OH positions of RNA aptamers can be substituted with 2'-F 82 , 83 , 84 , 2'-OMe 85 , 2'-NH 2 , 2'-LNA 86 , 87 , and 2'-d-/l-isonucleoside 88 , 89 . Substitution of non-natural nucleotides into oligonucleotides is achieved by mutating T7 RNA polymerase.…”
Section: Rna Modificationmentioning
confidence: 99%
“…Circular dichroism (CiD) [71], nuclear magnetic resonance (NMR) [72], X-ray crystallography [73] as well as molecular modeling [74] are useful to probe aptamer-target interactions. Using the structural information, the full-length aptamer can be subjected to post-SELEX to obtain the optimal sequence [75][76][77][78][79][80].…”
Section: Experimental Design Of Selexmentioning
confidence: 99%
“…BC15 (74 nt) is a DNA aptamer that was found by tissue slide-based SELEX, which has a high affinity to hnRNP A1 and A2/B1 ( Li et al, 2009 ), showing better antiproliferation activity in the HepG2 cell line ( Ku et al, 2015 ). We found that the core sequence of BC15, BC15-31 (31 nt), showed higher target affinity and further enhanced bioactivity and stability with isothymidine (isoT) modification at 5′- and 3′-terminal regions ( Li et al, 2018 ). Application of neutral cytidinyl lipid DNCA, through H-binding and π-π interaction, to reduce or avoid the use of cystine-based cationic lipid CLD ( Ma et al, 2016 ), gave a safe and effective delivery system for oligonucleotides ( Ma et al, 2018 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%